SOME PROBLEMS WITH ORDERING AND ENFORCING THE SECURITY MEASURE PROHIBITING OFFENDERS FROM OPERATING MOTOR VEHICLES - Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The subject of this paper is the prohibition on operating motor vehicles as a security measure ordered against offenders who have commited crimes which endanger traffic. The first part of the paper explains certain aspects of ordering this security measure. Special consideration will be given to ordering this measure against defendants who have not passed the driving test, as well as against offenders with a foreign driver's license. In the second part of the paper we will describe the enforcement of this security measure. Finally,  we will present our own view on the matter, which also represents the main motive for writing this paper, and that is the question of sanctions in case the prohibition on operating motor vehicles is not adhered to. The Criminal code of the Republic of Serbia prescribes the possibility of revoking a suspended sentence in case the prohibition is not adhered to. If this security measure is not ordered with a suspended sentence, but with a different criminal sanction, the question is whether there will still be a sanction if the prohibition is not adhered to.